Using period analysis to timely assess and predict 5‐year relative survival for colorectal cancer patients in Taizhou, eastern China - Min Zhang; Yongran Cheng; Bicheng Chen; Runhua Li; Xiyi Jiang; Liangyou Wang; Tianhui Chen; Qi Liao; Jinfei Chen (Cancer Medicine)
Abstract Introduction While timely assessment of long‐term survival for patients with colorectal cancer (CRC) is essential for evaluation on early detection and screening programs of colorectal cancer, those data are extremely scarce in China. We aimed to timely and accurately assess long‐term survival for CRC patients in eastern China. Methods Patients diagnosed with CRC during 2004–2018 and followed up until December 31, 2018 from four cancer registries with high‐quality data from Taizhou, eastern China were included. Period analysis was used to calculate 5‐year relative survival (RS) for overall and the stratification by sex, age at diagnosis and region. The projected 5‐year RS of CRC patients during 2019–2023 was also assessed using a model‐based period analysis. Results Overall 5‐year RS for patients with CRC during 2014–2018 reached 78.8%, being 74.9% for men and 86.1% for women. 5‐year RS declined along with aging, decreasing from 84.1% for age < 45 years to 48.9% for age > 74 years, while 5‐year RS for urban area was higher compared to rural area (83.9% vs. 75.8%). Projected overall 5‐year RS of CRC patients could reach 85.9% during the upcoming period 2019–2023. Conclusions We provided, for first time in China using period analysis, most up‐to‐date 5‐year RS for patients with CRC from Taizhou, eastern China and also found 5‐year RS for CRC patients have improved greatly during 2004–2018.